Feminist Collections, v.19, no.1 (fall 1997) - (:unkn) unknown (My University, 1997)
Subtitle: A Quarterly of Women's Studies Resources. 55p.
Contents: FROM THE EDITORS. BOOK REVIEWS: Women's Paradoxical Status in Contemporary China, by Judy Polumbaum. Between East and West: Chinese Women in Transition, by Hongjun Su. A Woman's Position in Gender Relations in Post-Mao China: An Alternative Perspective, by Hongjin Kang. Women and Gender in Africanist Research: A New Wave? by Susan O'Brien. New Locations of African Women's Writing, by Roberta Hatcher. FEMINIST VISIONS: "Discovering Women" Series Focuses on Women Scientists, by Carolyn Shaffer. TEACHING, LEARNING, AND DISTANCE EDUCATION IN WOMEN'S STUDIES, by Margaret Rozga. WORLD WIDE WEB REVIEW: The Elusive Quality of Web Quality, by Susan Barribeau. SPECIAL SECTION: WOMEN AND THE ONLINE WORLD: Getting Around Online: How, Where, Why? by Elisabeth Binder. The Gendered Bodies of Cyberspace, by Diana Saco. COMPUTER TALK: Compiled by Linda Shult NEW REFERENCE WORKS IN WOMEN'S STUDIES: Reviewed by Phyllis Holman Weisbard and others. PERIODICAL NOTES: Compiled by Linda Shult. ITEMS OF NOTE: Compiled by Christina Stross. BOOKS RECENTLY RECEIVED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews; China; Africanist Research; Women and the Online World; Women Scientists; Distance Education; Web Evaluation